PELATIHAN PENULISAN PUBLIKASI ILMIAH SEBAGAI UPAYA PEMENUHAN ANGKA KREDIT BAGI GURU-GURU DI JAWA TIMUR - Mustaji MMustaji (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2020)
In accordance with the mandate of the Minister of State Regulation on The Empowerment of State Apparatusand Bureaucratic Reform No. 16 of 2009 on the Functional Department of Teachers and Credit Figures Onecomponent of scientific publications assessed for the needs of teachers is the writing of class action researchreport. Teacher activities that produce class action research reports. Not all teachers want to work.Moreover, on the other hand, there are still many cases of plagiaris selling scientific papers in the world ofEducation. Teachers from different regions have partly written Class Action Research Reports, but manyare still unable to write Class Action Research Reports. The purpose of this activity is to improve the skillsof teachers in writing Class Action Research reports based on Credit Score Assessment. The target groupin this activity is teachers at the primary and secondary education level in East Java who have an interestand have great potential in writing the Education Class Action Research Report. The activities are carriedout in 5 stages, namely analysis of training needs, design, development, implementation, and evaluation.The results show that teachers already have the knowledge and skills to write Class Action Research reportsin accordance with credit score assessment standards.